Use of proton pump inhibitors and risk of iron deficiency: a population‐based case–control study - Tran‐Duy, A.; Connell, N. J.; Vanmolkot, F. H.; Souverein, P. C.; Wit, N. J.; Stehouwer, C. D. A.; Hoes, A. W.; Vries, F.; Boer, A. (Journal of internal medicine, 2019)
Background Hypochlorhydric states are an important cause of iron deficiency (ID). Nevertheless, the association between therapy with proton pump inhibitors (PPIs) and ID has long been a subject of debate. This case–control study aimed to investigate the risk of ID associated with the use of PPIs using the UK Clinical Practice Research Datalink (CPRD) database. Methods Cases were patients aged 19 years or older with first‐time diagnosis of ID between 2005 and 2016 (n = 26 806). The dates of first diagnosis of ID in cases defined the index dates. For each case, one control was matched by age, gender and general practice. A PPI “full” user (PFU) was defined as a subject who had received PPIs for a continuous duration of at least 1 year prior to the index date. A PPI “limited” users (PLU) was a subject who intermittently received PPI therapy. A PPI non‐user (PNU) was a subject who received no PPI prescriptions prior to the index date. The odds ratio of ID in PFU and PLU compared to PNU was estimated using conditional logistic regression. Results Among cases, 2960 were PFU, 6607 PLU and 17 239 PNU. Among controls, 1091 were PFU, 5058 PLU and 20 657 PNU. Adjusted odds ratio of ID in PFU and PLU compared to PNU was 3.60 (95%CI, [3.32–3.91]) and 1.51 (95% CI, [1.44–1.58]). Positive dose–response and time–response relationships were observed. Conclusions Chronic PPI use increases the risk of ID. Physicians should consider this when balancing the risks and benefits of chronic PPI prescription. Click here to view the Letter to the Editor by Dr. Jolobe.